Kadar Glukosa Darah Puasa dan Dihubungkan dengan Kualitas Hidup pada Pasien Ulkus Kaki Diabetik - Fahrun Nur Rosyid; Supratman Supratman; Beti Kristinawati; Diah Ayu Kurnia (Jurnal Keperawatan Silampari, 2020)
The purpose of this study was to assess fasting blood glucose (GDP) levels and correlate with quality of life in patients with diabetic foot ulcers (UKD). The design of this study uses clinical-based cross-sectional research. The results of this study found that most of the GDP levels in the category of hyperglycemia were 31 patients (62%) and a small proportion of hypoglycemia were 5 patients (10%). Quality of life was mostly good as many as 43 patients (86%) and a small proportion of poor as many as 7 patients (14%). Most of the GDP levels in the category of hyperglycemia with good quality of life were 17 patients (34%) and a small percentage of GDP with normoglycemia category with a good quality of life were 1 patient (2%). Statistical test results showed that the level of GDP was significantly related to quality of life in UKD patients (p = 0.04). Conclusions, GDP levels are significantly related to quality of life in UKD patients. Keywords: Diabetes mellitus, GDP levels, Quality of life, Diabetic foot ulcers